THE IMPACT OF JOB STRESS AND MOTIVATION ON TEACHERS’ PERFORMANCE IN SEKOLAH DASAR AND SEKOLAH MENENGAH PERTAMA SWASTA PERTIWI PONTIANAK - B12111019, FITRIANA WACHYUNIE (Jurnal Manajemen Update, 2015)
Rapid changes happen in Economy and technological development require every human resource to increase their ability and capability to compete with each other. Because human resource is an important aspect in an organization, all of organization would choose the best human resource to be placed in their company. Education institution is aim to build and create best human resources for the future. The implementation of education process is expected to produce qualified and high competitiveness human resources to face competition in the era of globalization. Improving the quality of human resources is the emphasis of educational purposes. To achieve the goals of the institution educator or teachers should have a good or better performance. The performance of the teachers can be affect by various factors such as job stress and motivation. The purpose of this study is to examine the impact of Job stress and Motivation on Teachers’ performance. Primary data was gathered using questionnaire base on 40 Teachers of SD and SMP Swasta Pertiwi Pontianak, interview with Headmaster, and observation. The results of the study revealed that Job stress have negative significant impact on Teacher’ performance and Motivation have positive significant impact on Teacher’ performance. Keywords: Job stress, Motivation, and Teachers’ Performance.